544 - Validation of a new cognitive screening tool, the Brain Health Test-7, for identification of mild cognitive impairment and early dementia in 3 differentkinds of hospital settings. (October 2021) - Shie, Meng-Shiuan; Loi, Mei Xian; Chen, His-Chung; Hsieh, Ming-Hsien; Lin, Yi-Ting; Liu, Chen-Chung; Wang, Pei-Ning; Chen, Jiahn-Jyh; Chen, Cheng-Sheng; Hsu, Chih-Cheng; Hwang, Tzung-Jeng
Abstract : Background: The Brain Health Test-7 (BHT-7) is a revised tool from the original BHT, containing more tests about frontal lobe function. It was developed with theaim of identifying patients with mild cognitive impairment (MCI) and early dementia. Research objective: Here we report the validity of the BHT-7 versus the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) in differentpsychiatry or neurology clinics. Methods: Patients with memory complaints were recruited in this study from the outpatient clinic of psychiatry or neurology in 3 different kinds of hospitals. Allpatients underwent the evaluation of the BHT-7, MMSE, MoCA, and clinical dementia rating (CDR). The clinical diagnosis (normal, MCI, dementia) was made by consensus meeting, taking into account all available data. Demographic data and the scores of the MMSE, MoCA, and BHT-7 between groups were compared. Logistic regression was adopted for analysis of optimal cutoff values, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), receiver operating characteristic (ROC) curve, and the area under the ROC curve (AUC). Results: We enrolled a total of 1090 subjects (normal 402, MCI 317, dementia 371); of them, 705 (64.7%) were female. There was a statistically significant differencein age, years of education, and 3 cognitive test scores among the 3 groups. Compared with the MMSE and MoCA, the BHT-7 performed slightly betterthan MMSE and MoCA in differentiating MCI or dementia from the normalcontrols (Table 1). For BHT- 7, the cutoff point was 17 between normal andMCI, and 14 between normal and dementia. These cutoff points for BHT-7were consistent through 3 different clinical settings, but inconsistent for MMSE and MoCA. The testing time for the BHT-7 was about 5-7 minutes, shorter than that of the MMSE and MoCA. Conclusion: Compared with MMSE and MoCA, the BHT-7 showed slightly better performance in differentiating normal from MCI or dementia subjects. The testing time for the BHT-7 was shorter, and its cutoff points were consistent through different outpatient clinic settings. The results support that BHT-7 is auseful cognitive screening tool for MCI or early dementia in various hospital settings.